PENGARUH KUALITAS LAYANAN TATA USAHA TERHADAP KEPUASAN SISWA DI SMAK SANTO YOSEPH SANGATTA - Sitoro, Simunawir; Irma, Irma; Madu, Herdianus (LPPM University 17 Agustus 1945 Samarinda, 2025)
This research aims to determine the influence of the quality of administrative services on student satisfaction at Smak Santo Yoseph Sangatta. The problem formulation is whether there is an influence between the quality of administrative services on student satisfaction at SMAK Santo Yoseph Sangatta method. The analysis used in this research is a simple regression analysis method with the SPSS application. The sample in this study amounted to 112 respondents. The independent variable is the variable quality of administrative services and the dependent variable is student satisfaction.The results of the research show that the administrative service quality variable (X) partially has a positive and significant influence on student satisfaction (Y) with a t valuecount 11.410 > ttable 1,658. Based on the coefficient of determination (R) value obtained in this research of 0.542, this means that 54.2% of the student satisfaction variable can be explained by the administrative service quality variable (X). It can be concluded that the quality of administrative services consisting of physical evidence (tangible), empathy (empathy), reliability (reliability), responsiveness (responsiveness) and guarantees (assurance) simultaneously has a positive and significant effect on student satisfaction at SMAK Santo Yoseph Sangatta.